Antiproton chain of the FAIR storage rings. (26th November 2015) - Katayama, T; Kamerdzhiev, V; Lehrach, A; Maier, R; Prasuhn, D; Stassen, R; Stockhorst, H; Herfurth, F; Lestinsky, M; Litvinov, Yu A; Steck, M; Stöhlker, T
Abstract: In the Modularized Start Version of the Facility of Antiproton and Ion Research (FAIR) at Darmstadt Germany, the 3 GeV antiprotons are precooled in the collector ring and accumulated in the high energy storage ring (HESR). They are further accelerated to 14 GeV or decelerated to 1 GeV for the experiments with a high-density internal target. The powerful beam cooling devices, stochastic cooling and electron cooling will support the provision of a high-resolution antiproton beam. The other option of FAIR is to prepare the low energy, 300 keV antiproton beam connecting the existing storage rings ESR and CRYRING with HESR. Beam physics issues related with these concepts are described.